2002
DOI: 10.1385/abab:98-100:1-9:1025
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Different Carbon and Nitrogen Sources in Production of Rhamnolipids by a Strain of <E1>Pseudomonas aeruginosa

Abstract: Culture conditions involving variations in carbon and nitrogen sources and different C:N ratios were examined with the aim of increasing productivity in the process of rhamnolipid synthesis by Pseudomonas aeruginosa. In addition to the differences in productivity, the use of different carbon sources resulted in several proportions related to the types of rhamnolipids synthesized (monorhamnolipids and dirhamnolipids). Furthermore, the variation in nutrients, mainly the nitrogen source, resulted in different amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(17 citation statements)
references
References 25 publications
4
12
1
Order By: Relevance
“…Similar results were reported by Santos [14] using the P. aeruginosa PA1 strain. In that study, an air bubbling system failed to control foam formation.…”
Section: Biosurfactant Productionsupporting
confidence: 91%
See 3 more Smart Citations
“…Similar results were reported by Santos [14] using the P. aeruginosa PA1 strain. In that study, an air bubbling system failed to control foam formation.…”
Section: Biosurfactant Productionsupporting
confidence: 91%
“…Between the hours 12 and 48, high nitrogen and phosphorus consumption was evident, which apparently influenced biomass production and biosurfactant synthesis. It has been reported that these nutrients stimulate microbial growth [14]. By contrast, an older study demonstrated that bacterial growth and surfactant accumulation were not modified by the addition of phosphate and magnesium [26].…”
Section: Kinetic and Modeling Of Rhamnose Production Cell Growth Anmentioning
confidence: 93%
See 2 more Smart Citations
“…The growth medium (inoculum) contained (in g/L) glucose 10.0, BRY 11.0, NH 4 NO 3 5.7, MgSO 4 ·7H 2 O 0.2, Na 2 HPO 4 7.0, and KH 2 PO 4 3.0. The medium containing the inoculum was adjusted to pH 7 and sterilized at 121°C for 15 Min 11,12.…”
Section: Methodsmentioning
confidence: 99%